Assessing Maternal and Child-Care Best Practices in the Safe Motherhood Project: A Study on Women of Childbearing Age in Ntcheu District, Malawi - Mseu, Dennis; Nyasulu, Betty Mkwinda; Muheriwa-Matemba, Sadandaula Rose (Medicine and Medical Research: New Perspectives Vol. 2, 2024)
Maternal awareness of best practices and behaviors regarding childbearing and childcare significantly impacts children's developmental outcomes and overall survival. This influence is most critical during the formative years of childbearing. Knowledge about proper nutrition, health practices, immunization schedules, and early childhood education plays a substantial role. Moreover, understanding and recognizing the signs of common childhood illnesses and conditions are vital aspects of maternal behavior that contribute to a child's well-being. Providing a safe and stimulating environment that encourages children's physical, emotional, and intellectual development is also pivotal. In essence, the role of mothers and maternal figures is central to fostering healthy, resilient, and capable children who can thrive in their subsequent life stages. This chapter evaluates knowledge and practices of key maternal and childcare practices among women of childbearing age in the Safe Motherhood project, managed by the Ntcheu District Health Office in the Republic of Malawi. Safe Motherhood Project is a Malawi Government initiative that includes direct and indirect efforts to reduce maternal, neonatal, and child deaths, as well as disabilities resulting from pregnancy and childbirth by ensuring that every woman has access to a full range of high-quality and affordable sexual and reproductive health services. The focus is on the cross-sectional study that utilized both quantitative and qualitative data collection and analysis procedures. Data were also collected through a review of participant health records. Although the findings showed that all participants (n=400) had a general knowledge of maternal and child health care, they did not have comprehensive information, and only a few mothers were practicing the recommended key child health care practices. Only 42.4% (n=170) knew the appropriate number of visits a woman should make to the antenatal clinic, very few knew the appropriate time at which to access antenatal care, and slightly over half (50%, n=220) breastfed their babies exclusively. Some participants introduced supplementary feeds as early as a month after birth, and not all women delivered at the health facility. Failure to actively involve men and elderly women in maternal and child health issues had a negative impact on women’s ability to fully implement key maternal and childcare best practices. The findings suggest that it is crucial to actively involve men and elderly women in addressing maternal and child health issues in the Malawian context. In Malawi, the responsibility of raising a child does not solely rest on the mother but also on the entire village community. Elderly women serve as the guardians for women of childbearing age and hold valuable traditional knowledge that can greatly benefit young women. Additionally, it is essential to engage Community Nurse-Midwives in facilitating women’s groups to provide comprehensive antenatal information to mothers, enabling them to apply this knowledge in practice.